2021
DOI: 10.3390/s21113814
|View full text |Cite
|
Sign up to set email alerts
|

Recent Research for Unobtrusive Atrial Fibrillation Detection Methods Based on Cardiac Dynamics Signals: A Survey

Abstract: Atrial fibrillation (AF) is the most common cardiac arrhythmia. It tends to cause multiple cardiac conditions, such as cerebral artery blockage, stroke, and heart failure. The morbidity and mortality of AF have been progressively increasing over the past few decades, which has raised widespread concern about unobtrusive AF detection in routine life. The up-to-date non-invasive AF detection methods include electrocardiogram (ECG) signals and cardiac dynamics signals, such as the ballistocardiogram (BCG) signal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 65 publications
(199 reference statements)
0
3
0
Order By: Relevance
“…These monitoring devices can provide cardio-dynamic information, but the accuracy is currently affected by motion artefacts, measurement location, skin conditions, ectopic beats, peripheral vascular disease, poor skin contact, and limited battery life [ 44 , 55 ]. In contrast, BCG-based AF detection devices are usually cushions or mattresses [ 16 ], which keep individuals unaware of the test and reflect the status of the larger cardiovascular system [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These monitoring devices can provide cardio-dynamic information, but the accuracy is currently affected by motion artefacts, measurement location, skin conditions, ectopic beats, peripheral vascular disease, poor skin contact, and limited battery life [ 44 , 55 ]. In contrast, BCG-based AF detection devices are usually cushions or mattresses [ 16 ], which keep individuals unaware of the test and reflect the status of the larger cardiovascular system [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…BCG is a noninvasive technique for recording the weak vibration signal on the surface of the body transmitted by the cardio-dynamic force [ 15 ]. Over the past decade, the development of BCG-based AF diagnosis through machine learning (ML) and deep learning (DL) has been increasingly investigated [ 16 ]. Bruser et al extracted 17 time and time-frequency features of BCG signals from 10 patients, which were split into 856 nonoverlapping epochs with a length of 30 s each, and applied seven ML algorithms to classify AF, sinus rhythm (SR), and body movement [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Non-ECG-based measurements, such as blood pressure, are also feasible, as Verberk et al [15] demonstrated the ability to obtain a recall of 98% and a specificity of 92% in detecting AF using a blood pressure monitor. Another possibility is the use of a photoplethysmographic signal [16,17], which has achieved a sensitivity and specificity of, respectively, 97% (±3%) and 99% (±3%) [16], or even cardiac dynamics signals, such as the ballistocardiogram signal or the seismocardiogram signal [18].…”
Section: Review Of Existing Literaturementioning
confidence: 99%
“…Many unobstructive sensing methods observing vital signs, such as heartbeat and respiration, have been evaluated for integration into unobstructive vital sensors that are based on the detection principle of air pressure [6][7][8], water pressure [9], cameras [10,11], microphones [12], load cells [13][14][15], piezoresistive [16], capacitively-coupled electrodes [17], and piezoelectric films [1,[18][19][20][21][22][23][24][25][26][27][28]. Among these, the sheet-type vital sensor using polyvinylidene fluoride (PVDF) as the pressure-sensitive layer is one of the most promising vital 2 of 12 sensors from the perspective of sensitivity and adaptability to various measurement environments [1,18,[21][22][23][24][25][26][27][28]. When the PVDF pressure-sensitive layer is distorted by an external force, the direction of the dipole inside the PVDF layer changes, and an electric charge is induced in the electrode.…”
Section: Introductionmentioning
confidence: 99%